The Microbiology of surgical site infection in closed upper limb fractures: data from a prospective trauma registry - Hashmi, Pervaiz; Tashfeen Ahmad; Muhammad, Zehra Abdul (Journal of the Pakistan Medical Association, 2022)
The current study aims to determine the rate of surgical site infection, causal microorganism, and antibiotic sensitivity pattern in operated upper limb closed fractures at the Aga Khan University Hospital, Karachi. Cases presenting between June 2015 to October 2019, were selected from a single-centre, longitudinal, prospective orthopaedic trauma registry. Infection rate, causal microorganism, and antibiotic sensitivity pattern were determined up to six months after surgery. From among a total of 376 closed fractures, 12 encountered surgical site infection with some having late onset, giving an infection rate of 3% which is 1% higher than the international benchmark. Microorganism culture was performed on 5 (42%) patients out of which 2 (40%) were positive. Frequently used prophylactic antibiotics were first generation Cephalosporin and Co-amoxiclav in 9 (75%) patients, but all other the patients required other antibiotic categories. Five patients required implant removal with antibiotic coverage. K-wire insertion required prolonged antibiotic treatment. Most of the cultures were negative in spite of the presence of infection. Key words: Trauma registry, upper limb, closed fractures, wound infection.